Fatigue in Shift Work on Stamping Division Workers of PT. Toyota Motor Manufacturing Indonesia (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2020)
Various health problems are known from shift works. PT. Toyota Motor Manufacturing Indonesia (TMMIN) as a car manufacturing in Indonesia is a large industry that applies a shift work system for the workers. This study aims to see the relationship between shift work system in the Stamping Division of PT. TMMIN. The measurement works by using the reaction time method on the worker the shift (shift I/morning and shift II/night) and non-shift during the workday flash. Based on the average measurement of reaction time for the shift workers I was 284.79 milliseconds and shift worker II was 307.76 milliseconds. The risk of reaction time increase was 3.222 times due to shift works compared to non-shift workers. Based on the value of reaction time, shift workers in PT. TMMIN recommends a repair per shift after work on the eighth day for shift I and twelfth day for shift II.